2020
DOI: 10.1177/2633494120908709
|View full text |Cite
|
Sign up to set email alerts
|

What is new in the landscape of insulin-sensitizing agents for polycystic ovary syndrome treatment

Abstract: Polycystic ovary syndrome, the most common gynecological endocrinopathy, is burdened with a state of hyperinsulinemia and insulin resistance in 50–80% of affected women. Wherever the origin of these metabolic abnormalities lies, their pathogenetic role in determining, perpetuating, and worsening the clinical traits of the syndrome is ascertained. Many studies have already highlighted possible mechanisms: hyperinsulinemia and insulin resistance may contribute to hyperandrogenemia, chronic anovulation, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Growing evidence indicates that PCOS patients generally have IR and that insulin sensitizers play an important role in the treatment of PCOS. 20,21 SGLT inhibitors, a new class of antidiabetic drug, could ameliorate IR and improve insulin sensitivity in T2DM patients. 11,22 However, limited data are available on the efficacy of SGLT2 inhibitors in the treatment of PCOS patients with IR.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that PCOS patients generally have IR and that insulin sensitizers play an important role in the treatment of PCOS. 20,21 SGLT inhibitors, a new class of antidiabetic drug, could ameliorate IR and improve insulin sensitivity in T2DM patients. 11,22 However, limited data are available on the efficacy of SGLT2 inhibitors in the treatment of PCOS patients with IR.…”
Section: Discussionmentioning
confidence: 99%
“…The agonists of glucagon-like peptide-1 (GLP-1) receptor and the inhibitors of dipeptidyl peptidase-4 are widely used to treat T2DM and MetS [ 158 , 159 , 160 , 161 ], but they can also be used to correct the metabolic alterations and IR in PCOS women, as well as in pregnant women with GDM and T2DM [ 162 , 163 ]. It is shown that MF enhances the beneficial effect of liraglutide, a selective GLP-1 receptor agonist, on insulin sensitivity and glucose homeostasis.…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…T2DM is a complex disease associated with an increasing risk of some pathological conditions, including obesity, metabolic syndrome, atherosclerotic cardiovascular diseases, certain types of cancer, non-alcoholic fatty liver disease (NAFLD), neurodegenerative diseases, PCOS, dementia and metabolic complications of non-retroviral infection [ 5 , 37 , 38 , 39 , 40 , 41 , 42 ]. Growing evidence suggests that metformin may substantially inhibit or delay their progression and improve prognosis, when added to the standard therapy of all of the above-mentioned diseases [ 36 , 41 , 94 , 97 , 98 , 99 , 100 , 101 , 102 ]. Moreover, metformin is sometimes used as an adjunct agent, together with insulin, to treat patients with type 1 diabetes [ 103 , 104 ].…”
Section: Pleiotropic Effects Of Metforminmentioning
confidence: 99%